Green design in living and bedroom spaces: exploring environmental restorativeness and affective qualities of spaces - Bellini, Silvia; Miola, Laura; Sperduti, Alessandro; Caccaro, Alessia; Pinton, Enrico; Graffeo, Monica; Pazzaglia, Francesca (Frontiers in Psychology, 2025)
IntroductionPrevious research has suggested that the introduction of greenery into built environments has positive effects on individuals' physical and psychological well-being. However, these studies have primarily focused on public spaces, overlooking domestic environments. Additionally, different types of greenery and the influence of individual differences in environmental evaluations have not been adequately considered, all of which are the main objectives of this study.MethodA total of 331 adults (18–67 years old) evaluated various images of domestic interiors (bedrooms and living rooms) designed with different furnishing conditions (no greenery, with potted greenery, and integrated greenery), rating perceived restorativeness and the affective qualities of the spaces.ResultsResults showed that rooms with greenery were perceived as more restorative and associated with more positive affective qualities. The direct integration of plants into the furniture made the spaces more fascinating and less monotonous, but also more chaotic and less coherent compared to the use of potted greenery. Furthermore, individuals with higher openness to experience and a stronger connection to nature tended to evaluate environments as generally less chaotic.DiscussionOverall, the findings demonstrate that a biophilic design approach enhances perceived restorativeness and the evaluation of indoor spaces, thereby contributing to the overall well-being of their occupants.